Challenges in Teaching Reading Comprehension: An ESP Case in Indonesia - Maria Priscilla Viledy; Fazri Nur Yusuf (LPPM Universitas Advent Indonesia, 2025)
Teaching English for Specific Purposes (ESP) presents unique challenges, particularly in reading comprehension, as educators must tailor their approaches to meet the specific needs and contexts of learners, often requiring specialized vocabulary and content knowledge. In this study the researcher tries to explore educators’ perspectives on the difficulties they encounter in teaching reading comprehension within ESP contexts, aiming to identify effective strategies that can enhance learner engagement and understanding. A qualitative study was conducted, involving questionnaires and interviews with several English language instructors across various institutions. The findings reveal many challenges faced by educators. Educators struggle to balance language instruction with industry content while managing administrative workload and limited course hours. The lack of standardized textbooks and financial support complicates material development. Diverse student backgrounds, large class sizes, and varying proficiency levels demand flexible strategies. Limited institutional support and industry-aligned resources hinder effective instruction. This study highlights the need for better support, resources, and training to improve ESP instruction in Indonesia’s higher education system.